MENINGKATKAN SIKAP ILMIAH DAN PEMAHAMAN KONSEP MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) PADA MATERI KESETIMBANGAN KIMIA - Hajjah Sa'adah; Muhammad Kusasi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. Research on the use of inquiry learning model guidance (Guided Inquiry) on chemical equilibrium which aims to determine the activity of teachers, the activity of students, improving the scientific attitude of students, an increased understanding of the concept of students, and the students' responses. The study design was Class Action Research (PTK) with two cycles consist of planning, action, observation, analysis and reflection. The subjects were a class XI student of MIPA 2 SMAN 6 Banjarmasin total of 36 people. The research instrument is a test and non-test. The results showed an increase from the first cycle to the second cycle which includes the activity of teachers from both categories to be very good, the student activity category of active to very active, scientific attitude of students category enough to be very good, understanding the concept increased from 72.01% to 88.80%, a positive student response to the use of guided inquiry learning model (Guided Inquiry).Keywords: scientific attitude, understanding concepts guided inquiry